2021
DOI: 10.3389/fonc.2021.764758
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting the Place of Metastasis-Directed Therapy in Isolated Liver Metastases in Prostate Cancer: A Case Report

Abstract: Metastatic prostate cancer remains a challenge for clinicians. Metastases involve mainly the bone compartment and can manifest as oligometastatic disease. In this setting, the role of metastasis-directed therapies (MDT) including surgery and/or stereotactic body radiotherapy is currently evaluated. Visceral metastases are less common and have very poor prognosis in mPC. Whether treating isolated visceral metastases such as liver metastases with MDT could increase the prognosis remains unknown. We report the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Furthermore, in another case study, a 66-year-old man with PCLM treated with radiofrequency ablation to the liver had no LM recurrence for 42 months [93]. Additionally, Yeo et al showed the potential for microwave needle ablation and SBRT to target LM [94]. While these case studies demonstrate promise, they need validation in prospective randomized trials.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in another case study, a 66-year-old man with PCLM treated with radiofrequency ablation to the liver had no LM recurrence for 42 months [93]. Additionally, Yeo et al showed the potential for microwave needle ablation and SBRT to target LM [94]. While these case studies demonstrate promise, they need validation in prospective randomized trials.…”
Section: Discussionmentioning
confidence: 99%